The mechanism of transactive memory systems development in cross-organizational team: A case study using the Gioia methodology - ISHIYAMA, Nobutaka; MATSUI, Takanori (Japanese Journal of Administrative Science, 2025)
This study aims to elucidate the mechanism of transactive memory systems （TMS） development in the team with informational diversity and task complexity. As management issues become more complex and volatile, cross-organizational teams are gaining attention. TMS is useful for understanding teamwork in such cross-organizational teams accompanied by informational diversity and task complexity. However, for the TMS development, few studies focus on contextual factors including team member diversity and task complexity. Furthermore, it is not clear how TMS develops with such factors. To address these problems, we studied 14 cross-organizational teams, conducting semi-structured interviews with 19 informants, supplemented by observations of the teams. The grounded theory approach and the Gioia methodology were used to analyze the data. We found that, in teams with informational diversity and complex tasks; 1） 'relationship change between members' is required for progress of TMS development; 2） occurrence and resolution of discord is characteristic when TMS is developed ; 3） trial and error during poor teamwork phase is essential to realize 'relationship change between members'.